TANGGUNG JAWAB HUKUM ATAS KONSUMEN DALAM TRANSAKSI E-COMMERCE TERHADAP KESESUAIAN PEMBELIAN PRODUK PADA VIDEO PROMOSI PLATFORM TIKTOK DI INDONESIA - Martinelli, Imelda; Saputra, Vinshen; William, Lavienda; Licardi, Sigit (Universitas Ekasakti, 2023)
The implementation of online transactions in various countries, especially Indonesia, has made it easier for people who need services or goods to use the presence of online transactions. carried out by business actors that are directly related to consumer data security such as the Tiktok Platform. On the other hand, this study has a useful purpose to find out how the regulatory system and responsibility originate from the rules themselves for online transactions by consumers on the Tiktok platform, besides that this study also adds information about the regulations that have been implemented by our country in overcoming conflicts that have arisen. there is. which in this study requires clear regulations regarding the protection or confidentiality of personal data of online transaction users and discusses settlements carried out by business actors against consumers who have become victims in the scope of regulations found in the Indonesian state, namely being responsible by providing compensation. This can be a solution so that consumer protection is created and there are clear rules according to what the consumer wants so that online transactions cannot be misused by irresponsible parties. therefore it is necessary to have a defense against online transactions carried out by consumers in buying goods or just similar to regulations that already exist, namely Law no. 8 of 1999 regarding consumer protection. These regulations can be used as legal certainty or regulatory protection for consumers in conducting online transactions as a result of this being a defender of the rights of consumers who have been harmed by business actors.